FPGA control of wheelchair movement for paralyzed persons using Steady State Visual Evoked Potential signals - Sri Abinaya R, Kalyana Sundharam C, Marichamy P (International Journal of Advanced Science and Technology, 2020)
A paralyzed person has a restricted mobility, they depends on other human beings. Independent mobility is an important aspect for human life. For these paralyzed persons, FPGA (Field Programmable Gate Array) based Brain Computer Interface (BCI) system provides an enhanced solution. To improve the mobility of paralyzed persons, vision based Steady State Visual Evoked Potential (SSVEP) signals plays important role. Direction of wheelchair depends on the frequency range of the SSVEP signals. The movement of the wheelchair is controlled by variation in the concentration level of the person on the stimulus screen. The proposed system is based on Discrete Wavelet Transform for extracting the features like Mean, Variation of SSVEP signals. Directions for the movement of wheelchair can be detected using Support Vector Machine (SVM) depends on frequency level of the signal.